Molecular fingerprint and anti-carcinogenic properties of Turkish immortelle (Helichrysum italicum) essential oil - Cebi, Nur; Akman, Perihan Kubra; Kafa, Pelin Nalbant; Sagdic, Osman (TAYLOR & FRANCIS LTD, 2024)
Immortelle (Helichrysum italicum) essential oil is one of the most valuable essential oils with its commercial importance and favorable characteristic properties in various cosmetic products and food products. Current research performed a comprehensive characterization of Immortelle essential oil using powerful and robust analytical techniques. The relative volatile composition of the Immortelle essential oil from Turkey was determined by GC-MS (gas chromatography-mass spectrometry) technique. Thirty-eight volatile compounds were identified. Average total phenolic content and DPPH radical scavenging activities (IC50) were determined as 54.24 mg GAE/mL essential oil and 0.27 mg/ml, respectively. FTIR and Raman spectroscopy fingerprints were determined for chemical characterization. The thermal profile was obtained by DSC (differential scanning calorimetry) analysis. The Immortelle essential oil (12.5 mu g/mL) inhibited the growth of Caco 2 adenocarcinoma cells at the ratio of 48% without any deterioration in healthy L929 fibroblast cells according to the cytotoxicity analyses.
Keywords: Helichrysum italicum (Immortelle) essential oil; Chemical fingerprinting; Antioxidant; Volatile composition; Anticarcinogenic; DSC; FTIR; Raman; GC-MS; ROTH G. DON; EXTRACTS; Plant Sciences